2019
DOI: 10.1177/0300060518822213
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin regulates the miR-21/PTEN/Akt pathway and acts in synergy with PD98059 to induce apoptosis of human gastric cancer MGC-803 cells

Abstract: Objective PD98059 is a potent and selective inhibitor of mitogen-activated protein kinase. Substantial preclinical evidence has shown an anti-tumor effect of curcumin on various solid tumors. This study aimed to investigate whether curcumin synergistically acts with PD98059 in exerting anti-gastric cancer effects. Methods The cell counting kit-8 assay was used to detect cell proliferation of the human gastric cancer MGC-803 cell line. Flow cytometry was performed to detect apoptosis. Western blotting was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Overall, these results suggested that the miR-21/PTEN pathway mediated geniposide-induced cardioprotection against ox-LdL injury. In addition, studies have demonstrated the roles of the miR-21/PTEN pathway in tumor growth, migration and invasion (44,45). combined with previous studies regarding the protection of geniposide against tumor (15,46), miR-21/PTEN pathway may contribute to the antitumor effect of geniposide.…”
Section: Discussionmentioning
confidence: 83%
“…Overall, these results suggested that the miR-21/PTEN pathway mediated geniposide-induced cardioprotection against ox-LdL injury. In addition, studies have demonstrated the roles of the miR-21/PTEN pathway in tumor growth, migration and invasion (44,45). combined with previous studies regarding the protection of geniposide against tumor (15,46), miR-21/PTEN pathway may contribute to the antitumor effect of geniposide.…”
Section: Discussionmentioning
confidence: 83%
“…The anticancer effect of curcumin was considered to inhibit cell proliferation by suppressing multiple cell signaling pathways (8). For example, curcumin could induce apoptosis by regulating the miR-21/PTEN/AKT signaling pathway in MGC-803 cells (9). Furthermore, curcumin inhibited cell migration and invasion by regulating miR-99a and JAK/STAT signaling pathway in retinoblastoma cells (10).…”
mentioning
confidence: 99%
“…Administration of curcumin (5–40 μM) reduces expression of miR-21 to activate PTEN signaling (highest effect in high doses of curcumin). Then, Akt undergoes downregulation to suppress proliferation of GC cells [ 188 ]. To date, just one study has evaluated the efficacy of curcumin in targeting PTEN signaling in GC cells, and more studies will reveal different molecular pathways of curcumin action in targeting PTEN in GC cells.…”
Section: Antitumor Compounds Target Ptenmentioning
confidence: 99%